Presenting a Commercialization Model of Knowledge Emphasizing the Role of Science and Technology Parks in the Relationship Between University and Industry (A Case Study of Knowledge-Based Companies in the Central Province Science and Technology Park) - Davari, Narjes; Pardakhtchi, Mohammad Hassan; Ahmadi , Gholam Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The commercialization of knowledge and technology is an important part of the innovation process. Commercialization implies scaling up from prototype to mass production and gaining access to more resources. Methodology: This research, by nature, is exploratory and was conducted using a descriptive-analytical method based on grounded theory, aiming to identify the components of knowledge commercialization with an emphasis on the role of science and technology parks in Iran. In the qualitative part, purposive sampling was employed with 12 individuals, where this type of sampling involves selecting units of study based on the research goal rather than at random. In the quantitative part, stratified random sampling was used, and samples were selected for each of the groups mentioned above proportionally to their population relative to the entire statistical population, using the Krejcie and Morgan table, resulting in the use of 300 questionnaires and ultimately, 232 questionnaires were collected and analyzed. For data analysis, factor loadings, Cronbach’s alpha tests, composite reliability, and average variance extracted (AVE), the PLS algorithm was utilized. Findings: The findings indicated that ten dimensions have been identified as components of knowledge commercialization based on the role of science and technology parks: educational-scientific dimension, financial-economic dimension, management dimension, process structure dimension, communicational dimension, legal dimension, socio-cultural dimension, support dimension, opportunities dimension, and threats dimension. Conclusion: The results show that the cultural and communicational dimensions are the most effective components, and the threats dimension is the least effective component of knowledge commercialization.